Schools and Screens: A Watchful History - Cain, Victoria E. M. (Cambridge, Massachusetts : The MIT Press, 2021)
"Cain chronicles twentieth-century schools' experiments with screen media and investigates the contests over citizenship and civic education that emerged in reaction".
Keywords: Audio-visual education -- History -- 20th century -- United States; Educational technology -- History -- 20th century -- United States; Mass media in education -- United States; Education -- Effect of technological innovations on -- United States